Facial blindsight - Solcà, Marco; Guggisberg, Adrian G.; Schnider, Armin; Leemann, Béatrice (Frontiers in Human Neuroscience, 2015)
Blindsight denotes unconscious residual visual capacities in the context of an inability to consciously recollect or identify visual information. It has been described for color and shape discrimination, movement or facial emotion recognition. The present study investigates a patient suffering from cortical blindness whilst maintaining select residual abilities in face detection. Our patient presented the capacity to distinguish between jumbled/normal faces, known/unknown faces or famous people’s categories although he failed to explicitly recognize or describe them. Conversely, performance was at chance level when asked to categorize non-facial stimuli. Our results provide clinical evidence for the notion that some aspects of facial processing can occur without perceptual awareness, possibly using direct tracts from the thalamus to associative visual cortex, bypassing the primary visual cortex.